2020
DOI: 10.4314/ahs.v20i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Candida spp. and age-related disparities amongst women presenting with vaginitis at the Obstetrics and Gynaecology (O&G) Clinic in a Tertiary hospital in Port Harcourt, Nigeria

Abstract: Background: Vaginitis, an infection of the lower genital tract in women, is known to be triggered by the overgrowth of the vagina’s naturally occurring microorganisms. Objective: This study looked at the prevalence of Candida spp. and age-related disparities amongst women presenting with vag- initis at the Obstetrics and Gynaecology (O&G) clinic in a tertiary hospital in Port Harcourt, Nigeria. Methods: One hundred high vaginal swabs were collected from pregnant and non-pregnant women and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The study carried out by Denning et al shows that the candidiasis is highly prevalent in the women of age group 25-34 years which is in correlation to this study [23]. The study done by Mbakwem-Aniebo et al shows that the VC is more prevalent in the age group of 20-29 years which is also complementary to the findings of the present study [24]. The study carried out by Rati et al [25] and James et al [26] also states that the vulvovaginal candidiasis is more prevalent in the age group 20-29 years which resembles to the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The study carried out by Denning et al shows that the candidiasis is highly prevalent in the women of age group 25-34 years which is in correlation to this study [23]. The study done by Mbakwem-Aniebo et al shows that the VC is more prevalent in the age group of 20-29 years which is also complementary to the findings of the present study [24]. The study carried out by Rati et al [25] and James et al [26] also states that the vulvovaginal candidiasis is more prevalent in the age group 20-29 years which resembles to the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Findings showed that females preferred herbal to western medication possibly because genitourinary candidiasis is more prevalent in females than men. About 50% of women, mostly in the reproductive age bracket get multiple infection episodes of VVC [ 59 ] and thus, the great demand for herbal remedies. Vaginal infections like VVC affect female private parts [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is differences in the prevalence of candida vaginitis that has been linked to risk factors such as high sexual activity, use of contraceptives, poor hygiene and antibiotics/drug abuse as is common in the younger, more sexually active age-groups ( 37 ). So that, some studies have shown that the prevalence of candida increased significantly in women below 35 years.…”
Section: Discussionmentioning
confidence: 99%